2019
DOI: 10.30714/j-ebr.2019353194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium sulphate on liver ischemia/reperfusion injury in a rat model

Abstract: To investigate the protective efficacy of magnesium sulphate in a model of rat liver ischemiareperfusion (I/R) injury. Method: 32 adult female Wistar-Albino rats (250 to 350 g) were used in this experimental study. Rats were divided into 4 groups according to liver ischemia and magnesium sulfate application methods. Group 1 (C); control, group 2 (M); magnesium sulphate, group 3 (I/R); liver I/R, group 4 (I/R+M); I/R + magnesium sulphate treated. The blood samples were centrifuged for the study of aspartate ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…A recent study has evaluated the effects of MgSO4 on the hepatic ischemia/reperfusion damage in a rat model, and the results from 32 adult female Wistar-Albino rats revealed that MgSO4 administration pretreatment moderately decreased the liver damage through its antiinflammatory and anti-oxidant effects (22).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has evaluated the effects of MgSO4 on the hepatic ischemia/reperfusion damage in a rat model, and the results from 32 adult female Wistar-Albino rats revealed that MgSO4 administration pretreatment moderately decreased the liver damage through its antiinflammatory and anti-oxidant effects (22).…”
Section: Resultsmentioning
confidence: 99%